IS IT A HIDDEN HANDICAP? STUDENTS WITH SPECIFIC LEARNING DIFFICULTIES AND ITS PATTERNS OF STRENGTHS AND WEAKNESSES IN SCIENCE LEARNING - Maulina, Bania; Lukito, Alamsyah; Mardiana, Nana (LPPM Universitas Jambi, 2025)
The aim of the research is to explore the cognitive profiles patterns of strengths and weaknesses of children with specific learning difficulties and to assess how these profiles can inform individualized educational interventions. Using a collective case study approach, data were collected from four school-aged children (7–9 years old) with low academic performance through a mixed-method design involving parental interviews and comprehensive psychological testing. The Wechsler Intelligence Scale for Children-Revised (WISC-R) and the Marianne Frostig Developmental Test of Visual Perception were employed to assess intellectual ability, working memory, attention, and visual perception. Results revealed that all participants had average to very superior intellectual capacities, indicating that learning difficulties were not related to intelligence level. However, consistent patterns of weaknesses were identified in working memory, attention, and visual-motor coordination, while abstract verbal reasoning remained a cognitive strength. One participant exhibited a unique strength in perceptual organization, linked to enriched sensory interaction and high intellectual capacity. This research offers a novel perspective on recognizing specific learning difficulties through cognitive profiling rather than general academic performance. The findings underscore the importance of comprehensive assessments in identifying hidden handicaps and developing tailored educational strategies. The implication is clear: effective interventions must consider both cognitive strengths and weaknesses to support academic achievement and emotional well-being in children with specific learning difficulties.